Mid-Sized Italian Manufacturing Firms: A Panel Data Analysis on Profitability - MIGLIARDO, Carlo; SCHILIRÒ, Daniele (Journal of Advanced Studies in Finance, 2017)
This paper aims to provide an empirical analysis concerning the different aspects of profitability of the Italian manufacturing firms of intermediate size, namely medium and medium-large size companies, for the period 2004-2010. It analyzes various aspects of firm profitability relating corporate structures, that is, capital structure, risk component, asset composition, and growth opportunities. The study investigates firm profitability by using econometric panel-data techniques, such as the system dynamic GMM estimator that assures the robustness of our empirical analysis. One of the main results of our investigation is that we find asignificant and negative impact ofcapital structure (i.e. leverage and tangibility) and risk component on firm profitability.
Keywords: Mid-sized Italian firms; profitability; panel data; (GMM) generalised methods of moments